1995
DOI: 10.1007/bf02211374
|View full text |Cite
|
Sign up to set email alerts
|

Production of insulin-like growth factor binding proteins (IGFBPS) by human endometrial stromal cells is stimulated by the presence of embryos

Abstract: Endometrial stromal cells were able to synthesize and secrete IGFBPs to modify IGF action on embryo development. Secretion of IGFBPs was stimulated by embryonic signals and was hormonally dependent. The fact that IGFBP3 was more responsive to embryonic signals suggests that it may be important in early implantation. On the other hand, IGFBP1 production was highly responsive to both P and R, suggesting that it may be important throughout pregnancy. In addition, the fact that IGFBPs were located in endometrial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…64 Interestingly, the presence of embryo also upregulates the production of insulin-like growth factor binding proteins (IGFBPs) by human endometrial stromal cells. 65 Thus, it appears that endometrial receptivity during the mid-luteal phase of cycle is likely to be associated with differential activation and repression of various cohorts of genes in endometrium under progesterone action following signal inputs from viable, synchronously developing embryo.…”
Section: Embryo Endometrial Dialoguementioning
confidence: 99%
“…64 Interestingly, the presence of embryo also upregulates the production of insulin-like growth factor binding proteins (IGFBPs) by human endometrial stromal cells. 65 Thus, it appears that endometrial receptivity during the mid-luteal phase of cycle is likely to be associated with differential activation and repression of various cohorts of genes in endometrium under progesterone action following signal inputs from viable, synchronously developing embryo.…”
Section: Embryo Endometrial Dialoguementioning
confidence: 99%
“…In this study, endometrial expression of IGFBP3, IGFBP4 and IGFBP5 mRNA at day 7 of oestrous cycle was affected by nutritional treatments, being greater in TMR and HA than MA cows. The increased in IGFBP3 mRNA supports a stimulatory role of this protein during early pregnancy as it has been reported that its expression responds to embryonic signals (Liu, Mele, Catz, Noyes, & Rosenwaks, ) and theorized that it may aid in the transportation of systemic IGF to its target site (Robinson et al., ). Several studies demonstrated that during development IGF2 and IGFBP4 mRNA are co‐expressed with IGF2 in many tissues indicating a potential interaction between IGF2 and IGFBP4 in growth and a possibly reservoir of IGF within tissues (Ning, Schuller, Conover, & Pintar, ).…”
Section: Discussionmentioning
confidence: 69%
“…Vero cells, which promote early embryonic development in coculture [19], release IGFBP3 into the culture medium [20], and the culture medium containing the most IGFBP3 was the most effective at promoting development. In addition, granulosa cells [48,49], oviductal and endometrial cells [20,50], and liver cells [51,52] promote development of conceptuses in vitro, and these cells all secrete IGFBP3 [15,20,[53][54][55][56]. In all these coculture systems, IGFBP3 may be one of the factors that supports development.…”
Section: Discussionmentioning
confidence: 99%